Methodical approach to determination of passenger transportation attractiveness on railway transport - Bozhok, N. A. (Science and Transport Progress, 2014)
Purpose. Development of a methodological approach to determine the attractiveness of passenger traffic on the basis of competition factors. Methodology. The major factors of competition affecting the passenger traffic volumes were pointed out to achieve this purpose. Findings. There are 3 chief players in the market of passenger transport services in the long-distance: road, railway and air transport. Moreover, the competition between them is escalating. That is why there was a need for determination of railway transportation attractiveness. For this purpose the following factors of the competition were separated: price policy of a carrier; vehicle motion speed; term and rhythm of a trip; transportation quality. Each of these indicators is considered separately. As a result it gave the opportunity to construct an integrated indicator of passenger traffic attractiveness. Originality. The offered methodical approach to determine the passenger traffic attractiveness gives the opportunity to estimate it; as well it also considers the high-speed movement introduction in Ukraine. Practical value. The offered technique will give the opportunity to determine volumes of transportations more precisely. It is necessary for definition of quantity of a rolling stock for prospect.